Accountability of Financial Management at Babul Khair Mosque in Gorontalo City - Baculu, Irwan M.A; Muhibuddin, Muhibuddin (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
This article examines the financial accountability of the Babul Khair Mosque located in Tenda Village, Gorontalo City. This study aims to identify the financial management practices of the mosque and the level of transparency and accountability applied in the management of mosque funds. Using qualitative methods, data were collected through interviews with mosque administrators, direct observation of financial activities, and analysis of available financial reports. The study's results show that mosque financial management still faces various challenges. Although efforts are being made to maintain transparency, financial information has not been fully disclosed to the congregation, resulting in a decline in trust. Accountability in the recording and use of funds also shows deficiencies that could pose a threat to fund allocation. This study is expected to provide a clear picture of the importance of accountability in mosque financial management, as well as provide recommendations for administrators to improve financial management practices that are more transparent and accountable. Thus, it is hoped that this will increase congregational participation and strengthen trust in mosque administrators' management of funds.